Sumpah Nafy Al-'ilmi Menurut Undang-undang Keterangan Islam Di Malaysia - Wan Abdul Fattah Wan Ismail; Hasnizam Hashim; Zulfaqar Mamat; Lukman Abdul Mutalib; Ahmad Syukran Baharuddin; Norma Jusof (Intelligentia Resources, 2024)
Vol. 2, No. 2, 2021( pages: 25-37)